2013
DOI: 10.1128/jvi.01693-12
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Polyadenylate-Binding Protein 1 and Kaposi's Sarcoma-Associated Herpesvirus ORF57 in Accumulation of Polyadenylated Nuclear RNA, a Viral Long Noncoding RNA

Abstract: Polyadenylate-binding protein cytoplasmic 1 (PABPC1) is a cytoplasmic-nuclear shuttling protein important for protein translation initiation and both RNA processing and stability. We report that PABPC1 forms a complex with the Kaposi's sarcomaassociated herpesvirus (KSHV) ORF57 protein, which allows ORF57 to interact with a 9-nucleotide (nt) core element of KSHV polyadenylated nuclear (PAN) RNA, a viral long noncoding RNA (lncRNA), and increase PAN stability. The N-terminal RNA recognition motifs (RRMs) of PAB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 72 publications
(133 reference statements)
4
63
0
Order By: Relevance
“…With unique sequence composition enriched in charged and hydrophilic residues, IDPs and IDRs interact with numerous ligands to exert a high binding capacity and are common in multifunctional proteins, such as the ones in cell signaling and in the viral proteome (59). We confirmed in this study and based on other reports (3,5,7,14,16) that the identified N-terminal IDR within the first ϳ250 aa residues of ORF57 is a major binding interface for ORF57 to interact with numerous cellular partners and RNAs and is highly conserved among other homologues as determined with the ANCHOR software (60, 61) (data not shown). While the structured C-terminal domain of ORF57 might play a role for a cofactor to efficiently bind to the ORF57 IDR, the finding that RBM15 and SRSF3 bind to ORF57 in a mutually exclusive manner due to both proteins binding to the same site in the N-terminal IDR (7) excludes such a possibility.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…With unique sequence composition enriched in charged and hydrophilic residues, IDPs and IDRs interact with numerous ligands to exert a high binding capacity and are common in multifunctional proteins, such as the ones in cell signaling and in the viral proteome (59). We confirmed in this study and based on other reports (3,5,7,14,16) that the identified N-terminal IDR within the first ϳ250 aa residues of ORF57 is a major binding interface for ORF57 to interact with numerous cellular partners and RNAs and is highly conserved among other homologues as determined with the ANCHOR software (60, 61) (data not shown). While the structured C-terminal domain of ORF57 might play a role for a cofactor to efficiently bind to the ORF57 IDR, the finding that RBM15 and SRSF3 bind to ORF57 in a mutually exclusive manner due to both proteins binding to the same site in the N-terminal IDR (7) excludes such a possibility.…”
Section: Discussionsupporting
confidence: 84%
“…Although all ORF57 functions involve ORF57 association with an RNA target, this association also requires cellular proteins to function as ORF57 cofactors (14,15), and each of the ORF57-specific functions depends on a specific cofactor(s). This has been demonstrated by the observation that ORF57 stabilizes PAN RNA via interaction with PABPC1 (16), that ORF57 mediates K8 splicing by interaction with SRSF3 (7), that ORF57 enhances ORF59 expression by the suppression of SPEN-induced nuclear hyperpolyadenylation (4), and that ORF57 promotes vIL-6 translation by preventing Ago2, a major component of RISC complexes, from interacting with a microRNA binding site in vIL-6 RNA (6).…”
mentioning
confidence: 99%
“…Immunofluorescence Analysis (IFA) and Confocal Microscopy-Indirect immunofluorescence antibody staining was performed as described previously (16,17). Briefly HeLa and HaCaT cells grown on poly-D-lysine-treated glass coverslips were fixed with 4% paraformaldehyde in PBS for 20 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…It remains unknown how ORF57 association with PAN RNA protects the transcript from cellular decay, but the cytoplasmic poly(A)-binding protein, PABPC1 (described below) and ALYREF have been implicated in its mechanism (Li et al, 2012; Massimelli et al, 2011; 2013; Stubbs et al, 2012). ALYREF is a component of the nuclear mRNA export machinery that binds to ORF57 (Boyne et al, 2008; Majerciak et al, 2006; Malik et al, 2004; Nekorchuk et al, 2007; Reed and Cheng, 2005).…”
Section: How Does Pan Rna Accumulate To High Levels In Lytic Phasementioning
confidence: 99%
“…Interestingly, PABPC1 was also pulled down from cellular extract by a biotinylated MRE element but not a size-matched control (Massimelli et al, 2011; 2013) and PABPC1 binds to ORF57 in vitro (Massimelli et al, 2013). The same study reported that PABPC1 knockdown increases the accumulation of PAN RNA, suggesting a negative role for PABPC1 in PAN RNA accumulation.…”
Section: How Does Pan Rna Accumulate To High Levels In Lytic Phasementioning
confidence: 99%